ANALYSIS OF IMPACT FROM TEACHER CERTIFICATION - YUYUN ELIZABETH PATRAS; RAIS HIDAYAT; AMIRATUL HASANAH (Sriwijaya University Learning and Education International Conference, 2016)
This research applies qualitative research and study case as its method. The aim of this research is to describe professional competence and learning process improvement after teacher certification program in Bojongrangkas 02 Elementary School, Bogor. Triangulation is employed during the data collection, which is the combination of observation, interviews, and documentation. The data analysis consecutively consists of data reductions process, presentation, and conclusion. The data then is examined through credibility, transferability, dependability, and confirmability test. The subjects taken are three teachers who have been certified in Bojongrangkas 02 Elementary School. The result of the professional competence reveals that the teachers are able to master the fundamental notions of learning, handle the various students’ ability, prepare the learning program, cope with stake holders at the school, understand the learning subject well, prepare the lessons based on the curriculum and level of students’ development, conduct evaluation, and cultivate students’ personality. On the other hand, they need guidance in exploring the material, using an appropriate strategy and teaching media, using information technology and communication as well as doing self reflection. The result of learning process improvement reveals that most teachers are competent in conducting the pre-activity session in the learning process, mastering the material, and using the appropriate language. However, they still need guidance in finding the appropriate learning strategy, using teaching media, encouraging students’ participation and enthusiasm, and applying the post-activity session in learning process. It can be concluded that the certificate program is greatly beneficial although some teachers may still need some coaching. This need emerges, as, in the real situation, there are drawbacks that need to be addressed, especially those in the aspects of professional competence and learning process.